2005
DOI: 10.1080/09537100500163572
|View full text |Cite
|
Sign up to set email alerts
|

The mean platelet volume in patients with essential and white coat hypertension

Abstract: Mean platelet volume (MPV), a determinant of platelet function, is a newly emerging risk factor for atherothrombosis. The risk profile of white coat hypertension has not yet been completely clear. The present study was designed to evaluate MPV in white coat hypertensive subjects compared with essential hypertensive patients and normotensive subjects. We selected 36 essential hypertensive patients, 36 white coat hypertensive subjects and 36 normotensive control subjects matched for age, gender, and body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 25 publications
(24 reference statements)
5
44
0
1
Order By: Relevance
“…7 The literature on the association between MPV and stroke is inconsistent 8,9 and may also relate to the use of different methods to assess MPV and the variable time points used for MPV measurement after stroke onset. 10 Moreover, emerging evidence has shown that known cardiovascular risk factors, such as smoking, 11 diabetes mellitus, 12 obesity 13 and hypertension, 14,15 are associated with MPV. Prehypertension, as defined by the Seventh Joint National Committee, 16 includes those with systolic blood pressure ranging 120-139 mm Hg or diastolic blood pressure ranging 80-89 mm Hg, is identified as a predictor for developing hypertension 17 and a stage where the primary prevention of hypertension is possible.…”
Section: Introductionmentioning
confidence: 99%
“…7 The literature on the association between MPV and stroke is inconsistent 8,9 and may also relate to the use of different methods to assess MPV and the variable time points used for MPV measurement after stroke onset. 10 Moreover, emerging evidence has shown that known cardiovascular risk factors, such as smoking, 11 diabetes mellitus, 12 obesity 13 and hypertension, 14,15 are associated with MPV. Prehypertension, as defined by the Seventh Joint National Committee, 16 includes those with systolic blood pressure ranging 120-139 mm Hg or diastolic blood pressure ranging 80-89 mm Hg, is identified as a predictor for developing hypertension 17 and a stage where the primary prevention of hypertension is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that there is a close relationship between MPV and cardiovascular risk factors, such as metabolic syndrome, diabetes mellitus, hypertension and hypercholesterolemia [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Large platelets express higher levels of prothrombotic substances, thromboxane A2, serotonin, b-thromboglobulin, and procoagulatory surface proteins, such as P-selectin and glycoprotein IIIa. [6,7] Increased MPV is associated with gestational diabetes mellitus, [8] congestive cardiac failure, [9] hypertension, [10] hypercholesterolemia, [11] and smoking. [12] Therefore, we excluded all patients having and of the above mentioned diseases to reduce the confounding effect in our statistical analysis.…”
Section: Discussionmentioning
confidence: 99%